The B56γ3-containing protein phosphatase 2A attenuates p70S6K-mediated negative feedback loop to enhance AKT-facilitated epithelial-mesenchymal transition in colorectal cancer - Kai-Ching Hsiao; Siou-Ying Ruan; Shih-Min Chen; Tai-Yu Lai; Ren-Hao Chan; Yan-Ming Zhang; Chien-An Chu; Hung-Chi Cheng; Hung-Wen Tsai; Yi-Fang Tu; Brian K. Law; Ting-Tsung Chang; et al. (Cell Communication and Signaling, 2023)
Abstract Background Protein phosphatase 2A (PP2A) is one of the major protein phosphatases in eukaryotic cells and is essential for cellular homeostasis. PP2A is a heterotrimer comprising the dimeric AC core enzyme and a highly variable regulatory B subunit. Distinct B subunits help the core enzyme gain full activity toward specific substrates and contribute to diverse cellular roles of PP2A. PP2A has been thought to play a tumor suppressor and the B56γ3 regulatory subunit was shown to play a key tumor suppressor regulatory subunit of PP2A. Nevertheless, we uncovered a molecular mechanism of how B56γ3 may act as an oncogene in colorectal cancer (CRC). Methods Polyclonal pools of CRC cells with stable B56γ3 overexpression or knockdown were generated by retroviral or lentiviral infection and subsequent drug selection. Co-immunoprecipitation(co-IP) and in vitro pull-down analysis were applied to analyze the protein–protein interaction. Transwell migration and invasion assays were applied to investigate the role of B56γ3 in affecting motility and invasive capability of CRC cells. The sensitivity of CRC cells to 5-fluorouracil (5-FU) was analyzed using the PrestoBlue reagent assay for cell viability. Immunohistochemistry (IHC) was applied to investigate the expression levels of phospho-AKT and B56γ3 in paired tumor and normal tissue specimens of CRC. DataSets of TCGA and GEO were analyzed to investigate the correlation of B56γ3 expression with overall survival rates of CRC patients. Results We showed that B56γ3 promoted epithelial-mesenchymal transition (EMT) and reduced the sensitivity of CRC cells to 5-FU through upregulating AKT activity. Mechanistically, B56γ3 upregulates AKT activity by targeting PP2A to attenuate the p70S6K-mediated negative feedback loop regulation on PI3K/AKT activation. B56γ3 was highly expressed and positively correlated with the level of phospho-AKT in tumor tissues of CRC. Moreover, high B56γ3 expression is associated with poor prognosis of a subset of patients with CRC. Conclusions Our finding reveals that the B56γ3 regulatory subunit-containing PP2A plays an oncogenic role in CRC cells by sustaining AKT activation through suppressing p70S6K activity and suggests that the interaction between B56γ3 and p70S6K may serve as a therapeutic target for CRC. Video Abstract